The relationship between safety management practices and safety behavior among operators in wire cable manufacturing company - Akmal Hannan, Md Shuhaime (2020)
“Prevention is better than cure”. Improving safety behaviour in workplace can prevent accident and reduce injuries among workers. The most important element that contributes to safety in an organization is safety management practices. The focus of this study is to determine the level of safety behaviour among operators and analyse the relationship between safety management practices and safety behaviour in a wire cable manufacturing company among the operators. This study used 5-point Likert scale questionnaires. The dimensions of safety management practices are management commitment, safety training, safety communication and feedback, worker involvement, safety rules and procedures and safety promotion policies. The dimension of safety behaviour is safety compliance. A total of 169 production department operators of 6 different plants were involved in this study. Data were analysed using descriptive statistic, correlation and multiple regression test via IBM SPSS. The findings of the study also revealed that safety promotion policies, safety rules and procedures and safety training were having positive relationship with safety compliance behaviour among operators in the company. Meanwhile, management commitment, worker involvement and safety communication and feedback have negative relationship with safety compliance behaviour among operators. The findings of the study will provide a good reference to the company to further improve their safety management practices in order to increase the level of safety behaviour among operators.